The Role of E-Commerce in the Management of Online Travel Agents - Evada Rustina; Dwi Endaryanti; Ade Riawan; Hastuti Pertiwi Bima Putri; Sumarwanto (International Journal of Economics, Business and Innovation Research, 2023)
The rapid development of technology encourages companies, especially in the hospitality sector, to follow the online sales market, one of which is Cavinton Hotel Yogyakarta. e-Commerce is part of Electronic Business which is carried out using electronic transmission by experts and business people. The purpose of this study is to examine how the role of E-Commerce in managing online travel agents at Cavinton Hotel Yogyakarta. This research uses a qualitative approach with data collection methods including observation, interviews, documentation and literature studies. From the results of the study, it was found that the role carried out by E-Commerce in managing an online travel agent to attract customers to book rooms at Hotel Cavinton Yogyakarta By Tritama Hospitality is very influential in increasing revenue.